Guidelines for clinical trials of frontal fibrosing alopecia: consensus recommendations from the International FFA Cooperative Group (IFFACG). (1st December 2021) - Olsen, E. A.; Harries, M.; Tosti, A.; Bergfeld, W.; Blume‐Peytavi, U.; Callender, V.; Chasapi, V.; Correia, O.; Cotsarelis, G.; Dhurat, R.; Dlova, N.; Doche, I.; et al.
Summary: Background: Frontal fibrosing alopecia (FFA) has become one of the most common causes of cicatricial alopecia worldwide. However, there is a lack of clear aetiology and robust clinical trial evidence for the efficacy and safety of agents currently used for treatment. Objectives: To enable data to be collected worldwide on FFA using common criteria and assessment methods. Methods: A multicentre, international group of experts in hair loss was convened by email to create consensus recommendations for clinical trials. Consensus was defined at > 90% agreement on each recommended part of these guidelines. Results: Standardized diagnostic criteria, severity rating, staging, and investigator and patient assessment of scalp hair loss and other clinical features of FFA were created. Conclusions: These guidelines should allow the collection of reliable aggregate data on FFA and advance efforts in both clinical and basic research to close knowledge gaps in this condition.